A Novel Coherent Multilevel Combined Phase and Polarization Shift Keying Modulation in Twisted Fibers. Issue 4 (3rd September 2017) - Perrone, Pierluigi; Betti, Silvello; Rutigliano, Giuseppe Giulio
ABSTRACT: This article proposes a novel coherent multilevel modulation model that exploits polarization and phase of the field. This model is based on the possibility of coherent systems to use all the four degrees of freedom of the electromagnetic field. The proposed scheme is able, by applying a suitable twisting process to the optical fiber, to physically confine the polarization and the phase of the transmitted field within the phase sphere. In this way, with the same performances of existing systems, the receiver is considerably simplified because there is no longer need of birefringence tracking circuits.